2015
DOI: 10.1302/0301-620x.97b8.35062
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the gravity stress test and clinical signs in cases of isolated supination–external rotation-type lateral malleolar fractures

Abstract: We prospectively assessed the diagnostic accuracy of the gravity stress test and clinical findings to evaluate the stability of the ankle mortise in patients with supination-external rotation-type fractures of the lateral malleolus without widening of the medial clear space. The cohort included 79 patients with a mean age of 44 years (16 to 82). Two surgeons assessed medial tenderness, swelling and ecchymosis and performed the external rotation (ER) stress test (a reference standard). A diagnostic radiographer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Previously, an analysis of standard, non-stress radiographs alone was considered insufficient to determine the stability of the ankle mortise in patients with this type of isolated SER fracture (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). We also found that female sex and only two fracture fragments were independent factors for predicting ankle mortise stability.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Previously, an analysis of standard, non-stress radiographs alone was considered insufficient to determine the stability of the ankle mortise in patients with this type of isolated SER fracture (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). We also found that female sex and only two fracture fragments were independent factors for predicting ankle mortise stability.…”
Section: Discussionmentioning
confidence: 73%
“…However, due to its moderate reliability, the MRI offers limited value to clinical decisionmaking (15). Alternatively, manual external-rotation (ER) stress radiographs (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), gravity stress tests (16)(17)(18)(19), or weight-bearing radiographs (20)(21)(22) have been used to quantify possible dynamic instability. Computer tomography (CT) has mainly been used in research settings (23,24).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations